2008
DOI: 10.3732/ajb.2007320
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure and diversity in Ramonda myconi (Gesneriaceae): effects of historical climate change on a preglacial relict species

Abstract: The importance of the Mediterranean Basin as a long-term reservoir of biological diversity has been widely recognized, although much less effort has been devoted to understanding processes that allow species to persist in this area. Ramonda myconi (Gesneriaceae) is a Tertiary relict plant species restricted to the NE Iberian Peninsula. We used RAPD and chloroplast markers to assess the patterns of genetic structure in eight mountain regions covering almost the full species range, to identify the main historica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
38
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 82 publications
10
38
0
Order By: Relevance
“…Limited gene flow among populations is also in agreement with the strong genetic drift observed in certain populations (e.g., CA and ME), where many alleles were fixed. Finally, as has been documented in other long live Tertiary relicts, gene flow may have been interrupted during some historic periods, increasing isolation and therefore F ST values (Dubreuil, Riba, & Mayol, 2008; Rodríguez‐Sánchez, Guzman, Valido, Vargas, & Arroyo, 2009; Rodríguez‐Sánchez et al., 2008). …”
Section: Discussionmentioning
confidence: 89%
“…Limited gene flow among populations is also in agreement with the strong genetic drift observed in certain populations (e.g., CA and ME), where many alleles were fixed. Finally, as has been documented in other long live Tertiary relicts, gene flow may have been interrupted during some historic periods, increasing isolation and therefore F ST values (Dubreuil, Riba, & Mayol, 2008; Rodríguez‐Sánchez, Guzman, Valido, Vargas, & Arroyo, 2009; Rodríguez‐Sánchez et al., 2008). …”
Section: Discussionmentioning
confidence: 89%
“…The 2 species cooccur only in SE Serbia, establishing a sympatric zone with mixed syntopic populations (Stevanović et al, 1986b). On the other side of Europe, R. myconi survives in limestone gorges and humid mountain valleys of the Pyrenees (Pico and Riba, 2002;Dubreuil et al, 2008). They all prefer limestone rocks, but R. nathaliae can also be found on ophiolitic bedrock (Košanin, 1921;Stevanović and Stevanović, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of the Balkan and Mediterranean areas as a reservoir of genetic diversity has been supported by the numerous phylogeographic studies and has benefited from the application of molecular markers and theoretical models of population genetics. Recent studies have shown that this higher genetic diversity only holds at the regional scale and that most Mediterranean relict populations often have reduced withinpopulation genetic diversity and high genetic distinctiveness, in vitro thereby increasing their conservation interest (5).…”
Section: Introductionmentioning
confidence: 99%
“…1). Ramonda myconi (L.) Rchb., another member of Gesneriads, is found in northeastern Spain and the central Pyrenees (5,15). Because of beautiful flowers in lilac and violet colours with an orange-yellow centre and rosette leaves, these species are mentioned as decorative plants (1,2,7,9).…”
Section: Introductionmentioning
confidence: 99%